Marionetas, máscaras e subversão: considerações sobre as imagens de Ruka - Cruz, Miguel (CEM – Cultura, Espaço & Memória, 2020)
Starting from the idea of the filmic object as an image with images within, as well from Hans Belting’s considerations about an image as a cross between mental and physical images, I intend to reflect on the last film by Jiří Trnka, Ruka (1965). I will also consider, following Belting, the image as a symbolic entity, similar to a mask, and I will, according to these premises, expose the images within the image of Ruka. Some of the conceivable readings of this film will be presented, but it is suggested that many others are possible. It is considered that the alienation effect enhanced by the film allows the viewer to claim control over their interpretation, contributing to the subversive nature of this film, which will be the last topic addressed in this present article.